Perceived stress and satisfaction with life following the 2023 earthquake in Türkiye: investigating the effects of irrational beliefs and hope - Teke, Esra; Karaman, Hüseyin B. (Frontiers in Psychology, 2025)
IntroductionRecent earthquakes that struck Türkiye led to major destructions. Extensive body of research continues to investigate the psychological impacts of earthquake that can cause a broad range of public health problems. The present research aimed to examine perceived stress levels, irrational beliefs, hope levels and levels of satisfaction with life among individuals following the earthquake that occurred on 06 February 2023 in Türkiye.MethodsFour hundred and eighty two participants were enrolled in the research (Mage = 25.1 years, SD = 7.07). The research utilized Perceived Stress Scale, Dispositional Hope Scale, General Attitude and Belief Scale, and Satisfaction with Life Scale. For the data analysis, the SPSS 25 software package and the PROCESS macro version 4.2 were utilized.ResultsThe analyses showed significant correlations among the variables. The results for the model indicated that perceived stress levels were significantly associated with irrational beliefs, hope levels, and levels of satisfaction with life among individuals following the earthquake. In addition, perceived stress levels were indirectly associated with satisfaction with life through their relationships with irrational beliefs and hope.DiscussionThe results highlight how perceived stress influences life satisfaction directly and indirectly through irrational beliefs and hope. These findings underscore the necessity for protective interventions to enhance psychological wellbeing after earthquakes.